Pengaruh Implementasi Kebijaksanaan Pembinaan dan Pengawasan terhadap Efektivitas Pelaksanaan Otonomi Daerah - Prabowo, Hadi (Jurnal Bina Praja, 2019)
The regional autonomy implemented for more than two decades is not entirely a success. An evaluation of the regional governance shows that many of the regional heads are tangled in legal cases, have bad financial management, and some other problems in the different levels of government. As such, it is necessary to examine the implementation of the development and supervision policy which aims to ensure the effectiveness of the regional autonomy. This study used a mixed, two stages method, with a quantitative approach using multiple regression analysis and followed by the qualitative approach of triangulation and ASOCA (Ability, Strength, Opportunities, Culture, and Agility) analysis method. The population in this study is the whole autonomous region in Indonesia (542 regions) with a sample of 85 regions. The quantitative analysis showed significant influence between the implementation of policy and development and supervision to the effectiveness of the regional autonomy. The qualitative analysis supported the quantitative analysis result and found new the dominant factors that produce a new model (novelty) called HADI (Human resources, Acceptance, Development, and Innovation) as an alternative model of the development and supervision policy for the effectiveness of regional autonomy. This study concluded that the successful implementation of an effective regional autonomy is very much influenced by the implementation of the policy and that a HADI model could be used as an alternative solution to the problem.